10) should be T= 13/4 You multiply both equations by 4 and the least common multiply of 4,2. Then 8 x 4 + 3 - 4t = 2 ( 5 x 2 +1 ) multiply 8 and 4 to get 32. Add 32 and 3 to get 35. Then you multiply 5 and 2 = 10 add 10 and 1 = 11 multiply 2 and 11 = 22 eventually ur equation should look like 35 - 4t =22 so you subtract 35 from 35 and 35 from 22 = -13 then you should have ur equation; -4t = -13 then you divide -4 by -4 = t so T = -13 /-4 but you simplify-13/-4 and switch the negative signs to positive ; 13/4